UTILIZATION HARVEST WASTE AS ORGANIC FERTILIZER BY COMPOSTING ON PADDY FARMER GROUP AT HUTAGAOL PEATALUN VILLAGE, BALIGE KABUPATEN TOBA SAMOSIR - Dermawan Hutagaol; Aisyah Lubis; Nurma Ani (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2016)
Paddy sawah cultivation that done for long time used chemical fertilizer with dosage that continously increased but many reports indicated no respond on increasing paddy production. Utilization of chemical fertilizer caused decreased soil quality, which fertilizer respond was less that indicated by production that hard to increase while fertilizer dosage was increased every year so farm cost more expensive especially for buy fertilizer. This problem must be solved by applicated res earch result for farmer with utilized harvest waste as organic fertilizer by composting. This IbM activity aim was to used harvest waste as organic fertilizer by composting to decrease fertilizer cost and farmer income be increased. This activity target was found IPTEKS for farmer how processes to made harvest waste be organic fertilizer by composting to increased fertilizer efficiency so that chemical fertilizer can decreased. This activity result after socialized about utilization and composting processes was farmer understood and could made compost from harvest waste and increased farmer knowledge abaout utilization harvest waste as organic fertilizer.Key words: compost, farmer, harvest waste